Genotypic and Phenotypic Evaluation of Biofilm Production and Antimicrobial Resistance in Staphylococcus aureus Isolated from Milk, North West Province, South Africa - Marie Ebob Agbortabot Bissong; Collins Njie Ateba (MDPI AG, 2020)
Background: Biofilm formation in S. aureus may reduce the rate of penetration of antibiotics, thereby complicating treatment of infections caused by these bacteria. The aim of this study was to correlate biofilm-forming potentials, antimicrobial resistance, and genes in S. aureus isolates. Methods: A total of 64 milk samples were analysed, and 77 S. aureus were isolated. Results: Seventy (90.9%) isolates were biofilm producers. The ica biofilm-forming genes were detected among 75.3% of the isolates, with icaA being the most prevalent (49, 63.6%). The icaB gene was significantly (P = 0.027) higher in isolates with strong biofilm formation potentials. High resistance (60%-90%) of the isolates was observed against ceftriaxone, vancomycin, and penicillin, and 25 (32.5%) of S. aureus showed multidrug resistance (MDR) to at least three antibiotics. Five resistance genes, namely blaZ (29, 37.7%), vanC (29, 37.7%), tetK (24, 31.2%), tetL (21, 27.3%), and msrA/B (16, 20.8%) were detected. Most MDR phenotypes possessed at least one resistance gene alongside the biofilm genes. However, no distinct pattern was identified among the resistance and biofilm phenotypes. Conclusions: The high frequency of potentially pathogenic MDR S. aureus in milk samples intended for human consumption, demonstrates the public health relevance of this pathogen in the region.